A Systematic Study of Staphylococcus aureus Biofilm Formation on Thiol‐Ene Polymers: Toward the Development of Microfluidic Bacterial Biofilm Models - Jéssica Amorim; Emil Rosqvist; Cristina D. Cruz; Markus Haapala; Jouko Peltonen; Päivi Tammela; Tiina M. Sikanen (Advanced Materials Interfaces)
Abstract Global antimicrobial resistance poses a major threat to human health and is largely driven by bacterial biofilms, which demonstrate significantly greater antibiotic resistance than planktonic bacteria. While most biofilm research targets the development of antibiofilm surfaces, materials that intentionally promote biofilm formation are crucial for creating screening tools to discover new antibiofilm agents. The transition from static to flow‐through assay systems is also necessary to increase the methodological readiness of antibiofilm research. This study evaluates the feasibility of an emerging polymer platform, off‐stoichiometry thiol‐ene (OSTE), in supporting Staphylococcus aureus biofilms. OSTE polymers provide versatile options for rapid prototyping of microfluidic devices, with unique opportunities for on‐chip oxygen management. Here, the impacts of OSTE's key materials properties on S. aureus adhesion, biofilm viability, biomass, and metabolic activity are systematically examined in comparison to polystyrene, the current standard in microwell plate‐based biofilm assays. Additionally, the composition of the extracellular polymer substances matrix and antimicrobial susceptibility are investigated to determine the most suitable OSTE composition for microfluidic S. aureus biofilm cultures. The results confirm compatibility with S. aureus biofilms, supported by atomic force microscopy analysis of biofilm morphologies under static and microfluidic conditions.